Development of a Comic Drawing Material Application for Eighth Grade Junior High School Students - Al-Haq, Zulfikar; Prasetyo, Abdul Rahman (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
Education in the technological era requires innovation in teaching methods to enhance student interest and understanding. One effective method is to utilize animation-based media, which can capture students' attention and facilitate a more enjoyable learning experience.In this context, the development of an animation application for drawing comics is expected to meet that need. This research aims to develop engaging and interactive learning media to enhance students' understanding of comic drawing material. The method used is the 4D model (Define, Design, Develop, Disseminate), which begins with the definition stage to identify the needs and learning objectives, followed by the design stage to design the content and application format, the development stage to produce and test the application, and the dissemination stage to distribute the application to students. The research results show that the developed animation-based application has high validity based on assessments by media and material experts, with a percentage above 85%. Field trials also showed a significant increase in students' interest in learning the comic drawing material, with an average test score improvement of 20% after using the application. Overall, this application has proven effective in supporting the comic drawing learning process in eighth-grade junior high school classes. This research plays a significant role in creating creative and interactive learning tools, as well as opening up opportunities for further research in the field of art education.